LAPORAN SUMBER DAN PENGGUNAAN DANA KEBAJIKAN BANK SYARIAH (STUDI PADA BANK MUAMALAT INDONESIA) - Rudi Hartono (Budgeting: Jurnal Akuntansi Syariah, 2022)
The concept of Islamic banking requires Islamic banks to provide social services through qard funds, zakat, and other donation funds in accordance with sharia principles. One of the fundamental differences between Islamic banks, as well as other Islamic entities and conventional banks, is the use of social funds received by Islamic banks' zakat institutions and then distributed by Islamic banks. The purpose of this paper is to find out how to report sources and users of Islamic bank virtue funds (Study at Bank Muamalat Indonesia). This study uses secondary data sourced from the company's financial statements PT. Bank Muamalat Indonesia Tbk, namely reports on sources and uses of benevolent funds in 2019 and 2020 taken from the company's annual report. The data analysis method in this study is data reduction, namely summarizing, selecting the main things, presenting data, and verifying/conclusion. The results of the study show that reports on sources of Islamic bank virtue funds come from infaq, alms, the results of waqf management in accordance with applicable laws, returns on productive virtue funds, fines, and non-halal receipts, while reports on the use of Islamic bank virtue funds are used for productive benevolence funds. , donations, other uses for the public interest. The report on the source of Bank Muamalat Indonesia's benevolent funds comes from fines and non-halal receipts, while the use of Bank Muamalat Indonesia's benevolent funds is used for donations